Restoration of nocturnal blood pressure dip and reduction of nocturnal blood pressure with evening anti‐hypertensive medication administration in pediatric kidney transplant recipients: A pilot randomized clinical trial. (7th October 2020) - Sethna, Christine B.; Grossman, Lindsay G.; Dhanantwari, Preeta; Gurusinghe, Shari; Laney, Nina; Frank, Rachel; Meyers, Kevin E.
Abstract: Non‐dipping and nocturnal hypertension are commonly found during ABPM in pediatric kidney transplant recipients. These entities are independently associated with increased cardiovascular disease risk in adults. Kidney transplant recipients aged 5‐21 years with eGFR > 30 mL/min/1.73 m 2 and ABPM demonstrating non‐dipping status and normal daytime BP were randomized to intervention (short acting BP medication added in the evening) or control (no medication change) in this pilot, randomized, open‐label, blinded end‐point clinical trial. ABPM, echocardiography, and PWV were performed at baseline, 3 months, and 6 months. The trial included 17 intervention and 16 control participants. Conversion to dipper status occurred in 53.3% vs 7.7% ( P  = .01) at 6 months for intervention and controls, respectively. Systolic dip was greater in the intervention group compared to controls (10.9 ± 4.5 vs 4.2 ± 4.6, P  = .001), and average systolic nighttime BP was significantly lower in the intervention group (106 ± 8.3 vs 114.9 ± 9.5 mm Hg, P  = .01) at 6 months. There were no significant differences in LVMI, PWV, or eGFR between groups. Within‐group changes in the intervention group demonstrated improvements in non‐dippers, dipping, systolic nighttime BP and nighttime BP load. Restoration of nocturnal dip and improvement in nocturnal BP were observed in the population following chronotherapy. Future studies are needed with larger sample sizes over a longer period of time to delineate the long‐term effect of improved nocturnal dip on target organ damage.